MODERN LEADERSHIP APPROACH: DIGITAL LEADERSHIP IN THE COMPLEXITY OF THE DIGITAL AGE - Arsyad, Arsyad; Sobandi, Ade; Hibrida, Anas Romzy (JMK (Jurnal Manajemen dan Kewirausahaan), 2025)
The complexity of the digital age has changed the business landscape and demanded organizations to transform profoundly. A modern leadership approach known as digital leadership is essential to managing this dynamic. Digital leadership refers to the ability of leaders to leverage digital technology to create innovation, drive organizational change, and maintain competitiveness in the global market. This approach involves a combination of technical competence, adaptability, and managerial skills to manage human resources, technology, and a dynamic business environment. This study reveals that digital leadership plays a key role in driving innovation, accelerating digital transformation, and creating resilient and sustainable organizations. The study also highlights the importance of integrating digital leadership in organizational strategies to create an adaptive, inclusive, and customer-oriented work culture. This study recommends the development of training and development programs to equip leaders with relevant competencies, the adoption of agile work methodologies, and the application of data analytics as the basis for strategic decision-making. Digital leadership is not only a solution to the challenges of the digital era, but also a catalyst for transformation to create an organization that is ready to face the future.